The role of disjoining pressure on the drying shrinkage of cementitious materials - Syeda Rahman (Open Geomechanics, 2024)
Drying induced shrinkage is often attributed to two major mechanisms- capillary pressure in the bulk pore solution and disjoining pressure in the liquid film separating the vapor phase from the pore wall or separating solid surfaces in nanometric pores. There is sufficient ambiguity in literature regarding the relative contribution of these two mechanisms, as well as the proper means to properly quantify their contributions. The objective of this manuscript is to evaluate the proper contribution of disjoining pressure in the drying shrinkage of cementitious materials. An unconventional approach to determining disjoining pressure within the framework of continuum mechanics is presented. This approach utilizes the conservation of linear momentum to derive a generalized expression of the disjoining pressure from the Lorentz force vector. The expression suggests that disjoining pressure is essentially an osmotic pressure at the contact surfaces that counters the electrostatic contribution to linear momentum. The proposed theory accurately predicts measurements of osmotic pressure found in the literature for the swelling of charged bilayers in a dilute salt solution. Applied to the shrinkage problem, the theory suggests that shrinkage stress is induced by the reduction in the potential gradient between the liquid film and bulk solution from the reference (fully saturated) state. The reduction in the potential gradient is caused by an increase in the concentration of the solutes in the pore solution when liquid water is removed as the relative humidity decreases.